Islamic Values Comprehension and its Correlation with Religious Tolerance Among High School Students - Adinda, Firhan; Musthofa, Indhra; al Anshori, Thoriq (LETIGES, 2025)
This study explores the relationship between students’ understanding of Islamic values and their attitudes toward religious tolerance in a multicultural school setting. As Indonesia continues to face challenges in maintaining interreligious harmony, this research aims to examine whether a stronger comprehension of Islamic teachings promotes more tolerant behavior among students. Using a quantitative correlational approach, the study involved 95 randomly selected Muslim students from a population of 952 at Senior High School 4 Malang City. Data were gathered through a closed-ended questionnaire and analyzed using descriptive and non-parametric statistics with SPSS 25.0. Findings show that 57% of students possess a moderate level of understanding of Islamic values, and 60% demonstrate a moderate attitude toward religious tolerance. The Spearman Rank test revealed a significant positive correlation (r = 0.418, p < 0.05), indicating that deeper knowledge of Islamic principles such as faith, worship, and moral conduct is associated with higher tolerance toward religious diversity. Although this study is limited to one public school and focuses solely on Muslim students, it offers meaningful implications for religious education. It suggests that Islamic Religious Education should not only emphasize cognitive knowledge but also nurture affective and behavioral aspects through contextual, dialogic, and experiential learning strategies. By doing so, schools can better cultivate inclusive attitudes among students. This research contributes empirical support to the idea that fostering Islamic values in a holistic manner can strengthen religious tolerance in Indonesia’s pluralistic educational landscape.